2015
DOI: 10.1016/s2213-2600(15)00331-8
|View full text |Cite|
|
Sign up to set email alerts
|

Sedation and analgesia practices in neonatal intensive care units (EUROPAIN): results from a prospective cohort study

Abstract: SummaryBackground Neonates who are in pain or are stressed during care in the intensive care unit (ICU) are often given sedation or analgesia. We investigated the current use of sedation or analgesia in neonatal ICUs (NICUs) in European countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
133
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(145 citation statements)
references
References 54 publications
4
133
0
2
Order By: Relevance
“…The first is the different prevalence of delirium in these populations. In our environment, agitated delirium does not exceed 8% in intubated patients whilst it is greater than 25% in non-intubated patients (6). A second reason is due to the different hazard presented by these patients.…”
mentioning
confidence: 75%
“…The first is the different prevalence of delirium in these populations. In our environment, agitated delirium does not exceed 8% in intubated patients whilst it is greater than 25% in non-intubated patients (6). A second reason is due to the different hazard presented by these patients.…”
mentioning
confidence: 75%
“…However, pain was not evaluated by scoring with a validated pain scale, because the hypothesis was established after recruitment of the sample; instead, the attendants used a combination of physiological and behavioral changes to estimate the pain in patients [10] , which we recognize as a study limitation. This limitation appears to be related to clinical practice in NICUs, where the majority of patients did not receive pain assessment with a scale, as was reported in a study of 30 NICUs where 16.7% of the neonates received a pain assessment with a scale [48] , while painful procedures such as tracheal intubation and cardiac surgery were assessed with pain scales in 58 and 56.7% of the neonates, respectively [41,49] . Another limitation was that DHA-containing oil had higher saturated fatty acids: lauric, myristic and palmitic, but lower linoleic and oleic acids compared with SO administered to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that 74% of neonates from 243 European NICUs received opioids during NICU stay, and the use of opioids were associated with prolonged duration of tracheal intubation, regardless whether they underwent a surgery [41] . Our result from the control group is consistent with above-mentioned study, but the DHA group remained at similar cumulative dose of buprenorphine ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…Each unit also kept a logbook of all neonates admitted during the study period. A centralized team in Paris monitored the completeness and relevance of the data entered in the study database, as reported in an earlier publication [21]. After obtaining the approval of the regulatory bodies for the Protection of Human Subjects, Data Protection, and Health Research Data Management in France, the study was also approved by the local ethical committees of the participating hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…The EUROPAIN survey is the first study, to our knowledge, to have prospectively recorded round-the-clock bedside A/S and PA practices for all NICU admissions over a defined period of time, generating a precise picture of these practices [21]. …”
Section: Introductionmentioning
confidence: 99%